A novel sensitivity analysis of a new integrated helium extraction process through the interaction of costs and environmental impacts. (August 2019) - Mehrpooya, Mehdi; Mood, Nazanin Ghollasi; Ansarinasab, Hojat; Alsagri, Ali Sulaiman; Mehdipourrad, Maysam
Highlights: Integrated flashing and distillation helium extraction process is investigated. The process is evaluated by Exergoeconomic/exergoenvironmental analysis methods. Cost of exergy destruction is calculated for the process equipment. Based on the results highest exergy destruction is related to the heat exchangers. Abstract: In this paper, a newly developed process configuration used for recovering helium from the natural gas, based on the integrated flashing and distillation method is investigated. The process is assessed by exergy cost and exergy environment based analysis mehtods. This analyses includes exergy analysis to assess efficiency of the helium extraction process, exergoeconomic analysis to present a relationship between economic costs and the performance of the extraction process, and exergoenvironmental analysis to identify the most environmental-effective components of the helium extraction process. Furthermore, a novel sensitivity analysis is used that links technical, economic, and environmental aspects of the process. From the results, it is shown that the developed process is able to separate Helium from the feed stream with higher performance (95%) comparing to the base ExxonMobil process (90%). Also, the most important elements in cost and environmental impact of exergy destruction are compressors used for pressurizing the outlet fuel gas from the process and the cold box used for cold recovery of outlet streams from the separation section due to high rate of irreversibility. To decline integrated process environmental impact, this cold box should be modified because the highest value of ( Y ̇ + B ̇ D ) belongs to this component. Also, based on the value of ( Z ̇ + C ̇ D ), these compressors should be modified to decrease the costs of integrated process.